Do Young Adults Interpret the DSM Diagnostic Criteria for Alcohol Use Disorders as Intended? A Cognitive Interviewing Study. (27th December 2012) - Slade, Tim; Teesson, Maree; Mewton, Louise; Memedovic, Sonja; Krueger, Robert F.
Abstract : Background: Estimates of the prevalence of DSM‐IV alcohol use disorders (AUD; i.e., abuse and dependence) are consistently higher for younger adults compared with their older counterparts. However, questions remain as to whether this "youthful epidemic" of AUD is real or a methodological artifact of the prevailing classification criteria. The aim of the current study was to explore potential shortcomings in the AUD criteria when applied to young adults. Methods: Experts in the field of substance use disorder classification carried out standardized appraisal of 4 DSM‐IV diagnostic criteria for alcohol abuse/dependence ( hazard, tolerance, larger/longer, quit/cut down ). Cross‐sectional surveys of 100 young adult drinkers aged 18 to 24 were carried out. All participants were administered a structured diagnostic interview as well as a structured cognitive interview. The cognitive interviews were comprised of a set of predetermined and standardized probe questions designed to shed light on young adults' understanding of interview questions designed to tap the AUD diagnostic criteria. Answers to the cognitive interview probe questions were summarized across the total sample and, where appropriate, comparisons were made between those who endorsed the diagnostic criterion and those who did not. Results: Results showed that there were substantial inconsistencies in young adults' interpretations of survey questions reflecting impaired control over alcohol. Interpretations of questions designed to measure tolerance to the effects of alcohol and use of alcohol in hazardous situations were largely understood as intended by the architects of DSM. Conclusions: Survey questions designed to tap compulsive patterns of alcohol use require close attention to ensure they reflect the intentions of the DSM diagnostic criteria for AUD.